2012
DOI: 10.1007/s00701-012-1312-6
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial arachnoid cyst family with autosomal recessive trait mapped to chromosome 6q22.31-23.2

Abstract: We present the first genetic linkage analysis result in a pure intracranial arachnoid cyst family in literature. Further investigation of this linkage area can reveal a causative gene causing the intracranial arachnoid cyst phenotype and can illuminate the pathogenesis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Parametric linkage analysis, a genetic mapping approach method, of consanguineous pedigrees has proven a powerful means for disease gene discovery in Mendelian disorders and is an important approach for identifying biological pathways relevant in common complex phenotypes. The logarithm of an odds ratio score method is broadly concerned with issues of power and the posterior probability of linkage, ensuring that a reported linkage has a high probability of being a true linkage [6,7]. We applied whole genome linkage analysis to our family where the father and mother were of a consanguineous marriage and had children with meningomyelocele.…”
Section: Discussionmentioning
confidence: 99%
“…Parametric linkage analysis, a genetic mapping approach method, of consanguineous pedigrees has proven a powerful means for disease gene discovery in Mendelian disorders and is an important approach for identifying biological pathways relevant in common complex phenotypes. The logarithm of an odds ratio score method is broadly concerned with issues of power and the posterior probability of linkage, ensuring that a reported linkage has a high probability of being a true linkage [6,7]. We applied whole genome linkage analysis to our family where the father and mother were of a consanguineous marriage and had children with meningomyelocele.…”
Section: Discussionmentioning
confidence: 99%
“…It was extrapolated that it originates from cellular remnants because of embryonic malformation as it was seen in intramedullary arachnoid cysts [11]. Bayrakli et al [12] reported genetic linkage of the intracranial arachnoid cyst and located chromosome 6q22.31-23.2.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Several mechanisms have been considered in the formation of arachnoid cysts such as splitting or duplication of the arachnoid membrane,[ 21 ] trauma,[ 8 ] and genetic factors. [ 4 ] Most are developmental anomalies. Acquired form of arachnoid cysts are associated with neoplasms, leptomeningitis, hemorrhage, or surgery.…”
Section: Discussionmentioning
confidence: 99%